Discrete hamstring: quadriceps strength ratios do not represent angle-specific ratios in Premier League soccer players - Lunn, D. E.; Nicholson, G.; Cooke, M.; Crespo, R.; Robinson, T.; Price, R. J.; Walker, J. (The Journal of Strength and Conditioning Research, 2023)
This study compared angle-specific hamstring:quadriceps (H:Q) ratios with their discrete counterparts during strength testing in professional male soccer players. Twenty-seven professional English Premier League soccer players were recruited for this study (age: 22 ± 4 years; stature: 1.81 ± 0.08 m; body mass: 74.7 ± 6.5 kg). Isokinetic testing of the knee flexors and extensors was conducted concentrically at two angular velocities (60° and 240°·s-1) and eccentrically (for the knee flexors only) at 30°·s-1. Conventional H:Q ratio was calculated as the ratio between peak joint moment in the flexors and extensors at 60°·s-1. Functional H:Q ratio was calculated as the peak joint moment in the flexors during the eccentric condition and the extensors at 240°·s-1. Discrete conventional and functional H:Q ratios were 0.56 ± 0.06 and 1.28 ± 0.22, respectively. The residual differences between discrete values and angle-specific residual values were 13.60 ± 6.56% when normalized to the magnitude of the discrete value. For the functional ratios, the normalized residual was 21.72 ± 5.61%. Therefore, neither discrete ratio was representative of angle-specific ratios, although the conventional ratio had lower error overall. Therefore, practitioners should consider H:Q ratio throughout the full isokinetic range of motion, not just the discrete ratio calculated from peak joint moments, when designing and implementing training programs or monitoring injury risk, recovery from injury, and readiness to return to play.